(untitled) (Itinera, 2019)
The paper aims to explore the theatrical success of Irène Némirovsky’s work, analysing in particular two Italian productions: Il Ballo, conceived and performed by Sonia Bergamasco, and the play Jezabel, adapted from the namesake novel by Maddalena Mazzocut-Mis and Sofia Pelczer, and directed by the latter. The analysis of these performances allows also to highlight the inherent theatrical dimension of Némirovsky’s work, both on a thematic and formal level. Némirovsky, representation, theatre, intermediality